Membangun Hubungan Positif antara Guru dan Anak di KB-TK se-Kecamatan Wonosari, Klaten - Fadillah, Galih Fajar; Harahap, Lukman; Argestya, Ulfa Fauzia; Wibawa, Angga Eka Yuda; Fajria, Aulia Rachma; Mu’alifah, Nurul (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
Building Positive Relationships between Teachers and Children in Kindergartens in Wonosari District, Klaten. A positive relationship between teachers and children is an important foundation in early childhood education that influences social-emotional and academic development. This community service activity aims to improve the understanding and skills of KB-TK teachers in Wonosari District, Klaten in building positive relationships with children. The community service method consists of several stages: planning, implementation, observation, and reflection. Participants involved used a stratified random sampling technique. The data collection instrument used interviews, questionnaires, and observations. The results of the interview and observation analysis showed the enthusiasm and interest of the participants, while the questionnaire results showed a significant increase in understanding before (pre-test) and after (post-test) (90% of participants experienced an increase in scores). The evaluation results also showed an increase in teacher readiness in implementing two-way communication strategies, providing positive affirmations, and an individual approach that is responsive to children's needs. This activity successfully strengthened teachers' relational capacity and is expected to create a conducive learning environment for the holistic development of early childhood in Wonosari District, Klaten.